MASS MEDIA AS A LEGAL COMMUNICATION SUBJECT - Макеєва, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Aim: in the article the mass media is researched as subject of legal communication with their functions. Methods of research: philosophical-ideological, general scientific and special methods were used in the work. Results: the idea of mass media as the subject of legal communication is defined, which are material and other carriers of legal information, bodies and organizations (legal entities) registered in the established procedure, which ensure the public distribution of legal printed and audiovisual information. The functions of mass media are outlined: law-educational, value-normative, law-oriented, communicative, warning, legal-socialization, ideological-educational. Discussion: improvement of the national information policy concerning the mass media needed, which provides the creation of legal basis for ensuring favorable conditions for the development and functioning of mass media as subjects of legal communication. Essential features of the media as the subject of legal communication are: publicity (unlimited, unpersonalised consumer circle); availability of special technical means; indirect, divided in space and time cooperation of communication partners; unstable nature of the audience; the overwhelming unidirectional effect from communicator to recipient. The task of the media is to convey information to consumers, which could be done in different ways (press, radio, television, electronic media). The form of ownership is distinguished by state and non-state (private) media. Legal communication is formed as a means of broadcasting normative information that establishes legal relations and legal understanding in society, contributes to improving the relationship between all elements of the legal system, law interpretation, law-making and law-enforcement activities in the state through the media. The functions of the media as the subject of legal communication are the main directions of media influence on the legal life of society in order to transfer and disseminate legal information while executing professional powers.